Proceedings of the Companion Publication of the 2014 Annual Conference on Genetic and Evolutionary Computation 2014
DOI: 10.1145/2598394.2609855
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of particle swarm optimization techniques in segmentation of biomedical images

Abstract: Image segmentation is a common image processing step to many computer vision applications with the purpose to segment pixels into different classes. As improved variants of particle swarm optimization (PSO) algorithms, the fractional-order Darwinian particle swarm optimization (FODPSO) and Darwinian particle swarm optimization (DPSO) have been proposed for image segmentation. The purpose of this paper is to compare the segmentation performance of PSO, DPSO, and FODPSO as parametric approaches to existing metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…PSO technique has shown its superiority over conventional thresholding algorithms including fuzzy C-means and Otsu techniques for multidimensional biomedical images, especially retinal blood vessel segmentation. 31,32…”
Section: En-face CVI Estimationmentioning
confidence: 99%
“…PSO technique has shown its superiority over conventional thresholding algorithms including fuzzy C-means and Otsu techniques for multidimensional biomedical images, especially retinal blood vessel segmentation. 31,32…”
Section: En-face CVI Estimationmentioning
confidence: 99%
“…They also compared the segmentation performance of PSO, DPSO, and FODPSO as parametric approaches to existing methods, namely the parametric fuzzy c-means (FCM) algorithm and the non-parametric Otsu segmentation technique, by applying the different techniques to five biomedical images. The obtained experimental results showed that particle swarm-based algorithms outperformed both FCM and Otsu segmentation techniques [5]. However, these methods easily fall into a local optimum due to the lack of dynamic adjustment of speed, which leads to low convergence accuracy and difficulty in convergence.…”
Section: Related Workmentioning
confidence: 99%
“…In the image segmentation framework, the pixel set matches to the lookup space, along with the optimum solution matches to exploiting the between-class deviation of the distribution of intensity degrees in the image. Following the notation in [27] notation, at time t each particle moves in a search space with position and velocity which are dependent on local best position neighborhood best and global best information as follows:…”
Section: Particle Swarm Optimization Techniquesmentioning
confidence: 99%
“…(2). The fitness function  used to evaluate the performance of the particles is given by [27] [28]:…”
Section: Particle Swarm Optimization Techniquesmentioning
confidence: 99%